2018
DOI: 10.1007/s40279-018-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training Versus Moderate-Intensity Continuous Training On Blood Pressure in Adults with Pre- to Established Hypertension: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: PROSPERO registration (2016: CRD42016041885).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
145
2
18

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(176 citation statements)
references
References 41 publications
11
145
2
18
Order By: Relevance
“…Therefore, there seems to be a greater trend for VO 2max -ES improvement in HIIT than in MICT. Our results are in accordance with various studies showing that the application of both HIICT and MICT succeeded in increasing the VO 2max values for subjects with cardiovascular diseases [4,24], as well as in healthy elderly and middle-aged people [38]. Similarly, in line with the better trend shown by HIICT, a meta-analysis showed that HIIT improved VO 2max more than MICT in overweight or obese adults [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, there seems to be a greater trend for VO 2max -ES improvement in HIIT than in MICT. Our results are in accordance with various studies showing that the application of both HIICT and MICT succeeded in increasing the VO 2max values for subjects with cardiovascular diseases [4,24], as well as in healthy elderly and middle-aged people [38]. Similarly, in line with the better trend shown by HIICT, a meta-analysis showed that HIIT improved VO 2max more than MICT in overweight or obese adults [39].…”
Section: Discussionsupporting
confidence: 92%
“…HIIT includes intervals of high-intensity aerobic exercise (85%-100% of VO 2max ) interspersed with periods of relative rest (0%-40% of VO 2max ) [22]. In fact, much research has shown strong evidence that HIIT is an effective method for improving VO 2 peak [21,23], BP [24,25] and post-exercise HR recovery [18,26] in people with cardiovascular diseases. Indeed, the literature shows a more favorable trend for HIIT than for MICT in improving health indices and markers [22].…”
Section: Introductionmentioning
confidence: 99%
“…The potential for blood pressure reduction is low, which may be related to the fact that our study did not include work based on hypertension. The absence of a significant difference in blood pressure reduction between HIIT and MICT was similar to the findings of previous systematic reviews and meta-analyses, indicating that HIIT and MICT could provide a similar decrease in SBP and DBP in adults with pre-to established hypertension (Costa et al, 2018). Campbell et al (2019) also demonstrated that a HIIT-induced blood pressure reduction was comparable with that of MICT in adults; people who were overweight or obese were more responsive in terms of blood pressure reduction than people with a normal weight.…”
Section: Discussionsupporting
confidence: 88%
“…These are pivotal aspects that impact metanalytic effect sizes [42]. Also, some studies did not assess the risk of publication bias [6,10,28,31,38,39,41,43], and those that did concluded that there was some evidence of publication bias [9,35,40].…”
Section: Completeness Of Reportingmentioning
confidence: 99%
“…Flow diagram of the inclusion process.Of the assessed SRMAs[6,[8][9][10][11][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] two were unpublished ) at the moment of our search strategy. All SRMAs were available at [or submitted to] specialty journals and none was a Cochrane Review.…”
mentioning
confidence: 99%